The discovery of a pan-genotypic, primer grip inhibitor of HCV NS5B polymerase12. Issue 4 (8th February 2017) - Eastman, Kyle J.; Parcella, Kyle; Yeung, Kap-Sun; Grant-Young, Katharine A.; Zhu, Juliang; Wang, Tao; Zhang, Zhongxing; Yin, Zhiwei; Beno, Brett R.; Sheriff, Steven; Kish, Kevin; Tredup, Jeffrey; et al.
Abstract : A series of novel 7-azabenzofurans exhibiting pan-genotype inhibition of HCV NS5B polymerase via binding to the primer grip site is presented. Abstract : The development of a series of novel 7-azabenzofurans exhibiting pan-genotype inhibition of HCV NS5B polymerase via binding to the primer grip site is presented. Many challenges, including poor oral bioavailability, high clearance, bioactivation, high human serum shift, and metabolic stability were encountered and overcome through SAR studies. This work culminated in the selection of BMS-986139 (43 ) as a preclinical candidate.